The Existence of the State of Brunei Darussalam in Advancing Education, Economy and Social Governance “Learning Reflections at the Sultan Syarif Ali University UNISSA Brunei Darussalam” - Sumarto Sumarto; Emmi Kholilah Harahap; Ilham Dwitama Haeba (International Journal of Southeast Asia, 2020)
As a prosperous and developed country, of course the State of Brunei Darussalam has implemented a very good education, economy and government system in accordance with the state ideology that is firmly held, namely Malay Islam Beraja (MIB). In the aspect of education, socio-economics and leadership in Brunei Darussalam embody Islam that is Rahmatan lil alamin according to the explanation we have conveyed. Education in Brunei Darussalam is characterized by the dominance of Islamic Religious Education which is specifically managed by Kesultanana in the Haji Sultan Hassanal Bolkiah Foundation (YSHHB) as well as at the tertiary level such as at UBD (Universiti Brunei Darussalam), KUPU (Kolej Universiti Perguruan Ugama) Seri Begawan and UNISSA (Sultan Sharif Ali Islamic University).The Sultanate government as fully responsible for the education process also integrates Islamic religious education with science, where according to the teachings in the Qur'an and Hadith, all have a connection and are beneficial to humans. Likewise with progress in the economic sector, where the State of Brunei Darussalam is a producer of oil and gas in Southeast Asia and even globally, which supports the welfare of its people. A government system that continues to maintain security and stability by adhering to the MIB ideology, carrying out Islamic teachings very well, this can be seen from every policy and regulation delivered by the Sultanate.